Towards autonomous lateral flow assays: Paper-based microfluidic fuel cell inside an HIV-test using a blood sample as fuel. (16th November 2017) - Dector, A.; Galindo-de-la-Rosa, J.; Amaya-Cruz, D.M.; Ortíz-Verdín, A.; Guerra-Balcázar, M.; Olivares-Ramírez, J.M.; Arriaga, L.G.; Ledesma-García, J.
Abstract: This work presents the integration of a paper-based microfluidic fuel cell inside a lateral flow assay-human immunodeficiency virus (HIV) test. To modify the HIV test, a bioanode that oxidizes the glucose present in a serum or blood sample and a cathode that reduces the oxygen delivered from air were stacked on the bottom and top, respectively, of a paper-strip test. A mixture of glucose oxidase enzyme, Nafion ®, glutaraldehyde, deionized water and tetrabutylammonium bromide were deposited on a methylene blue electro-polymerized Toray ® paper and used as the bioanode. Meanwhile, Pt/C (Vulcan XC-72) on Toray ® paper was used as an air-breathing cathode. The GOx enzyme anchored on the carbon-based surface was examined by scanning electron microscopy. The electrochemical response of the bioanode array demonstrated the oxidation of 0.1 M glucose, leading to a current density increase due to FAD + /FADH reactions. The above procedure was corroborated through scanning electrochemical microscopy, which showed an increase in the current (400 pA) in the presence of glucose on the bioanode. The paper-based microfluidic fuel cell performance showed power densities of 0.16 and 0.12 mW cm −2 using human serum and blood samples, respectively. Furthermore, the stability of the device was measured in terms of the recovery after obtaining four polarization curves that lasted 30 min, after which the sample dried out. This work represents a great advancement in the integration of a paper-based microfluidic fuel cell towards autonomous lateral flow assays. Highlights: The first paper-based microfluidic human blood fuel cell is presented. The microfluidic fuel cell was integrated in a lateral flow assay. The device was capable of delivering power density using blood as fuel. Gox enzyme was used as anode in the microfluidic fuel cell. This work shows a progress in the integration of fuel cell in medical device.